Penerapan Cullturally Responsive Teaching Terhadap Minat Belajar Siswa pada Mata Pelajaran Ekonomi Kelas X.4 di SMAN 1 Pekanbaru - Massuniarti Massuniarti; Muarti Muarti; Niken Ayu; Hendripides Hendripides; Mulyani Mulyani (Politeknik Kampar, 2025)
This study aims to analyze the implementation of the Culturally Responsive Teaching (CRT) approach in improving students' interest in learning Economics in class X.4 at SMAN 1 Pekanbaru. This approach emphasizes the appreciation of students' cultural diversity in the learning process. This research uses a descriptive approach with a qualitative method involving both teachers and students as research subjects. Data collection techniques include observation, interviews, and documentation. The results of the study indicate that the application of CRT creates more relevant and engaging learning for students, thereby enhancing their interest in learning. However, there are challenges related to students' independence in learning and the limitations of technological facilities that need to be addressed. Teachers' efforts in providing support and adapting the learning process have proven effective in overcoming these challenges. This research makes an important contribution to more inclusive teaching practices based on students' needs and cultural contexts.